Window functions and their applications in signal processing - Prabhu, K. M. M., author (Boca Raton, [Florida] : CRC Press/Taylor & Francis, 2014)
"It is well-established that the window functions play a vital role in digital signal processing. Sometimes, it becomes critical in selecting the right window for a given application. Major applications areas include digital spectral analysis, design of FIR filters, pulse compression radar, and speech signal processing. This book provides complete information on the discrete time window functions used in digital signal processing. It also gives cues on how to choose a window function for particular applications. Topics covered include spectral analysis, use of windows in digital filtering, application of windows in radar, and ringing artifacts applications of the Short Time Fourier Transform (STFT) in speech processing"--provided by publisher